English for academic purposes : - Jordan, R. R. (Cambridge University Press, 1997)
This book provides a comprehensive overview of the field of English for Academic Purposes (EAP) for teachers. It looks at study skills and other concerns, such as needs analysis, syllabus and course design, methodology and materials, learning styles, tests and exams, academic style and genre analysis.